Tren Inovasi Media Pembelajaran Matematika Berbasis Digital Di Sekolah Dasar: Studi Literature - Resty Yufrina; Elfia Sukma (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
The development of information technology has brought about significant transformations in the world of education, particularly in mathematics learning at the elementary school level. This study analyzes the trend of innovation in digital-based mathematics learning media in elementary schools through a literature review method of various scientific articles and journals. The results of the analysis show a shift in the trend from conventional or physical teaching aids to interactive digital media such as animated videos, educational games, multimedia, and Augmented Reality (AR), among others. Digital learning media has proven effective in increasing students' learning motivation, understanding of abstract concepts, and mathematical problem-solving skills. Despite its effectiveness, the implementation of digital learning media still faces various challenges in the form of gaps in technology access and limited digital competencies possessed by teachers. This study recommends the need for equitable distribution of digital-based infrastructure and continuous technology training for teachers at the elementary school level.